Modified activities of macrophages’ deubiquitinating enzymes after Francisella infection - Vozandychova, Vera; Rehulka, Pavel; Hercik, Kamil; Spidlova, Petra; Pavlik, Pavla; Hanus, Jaroslav; Hadravova, Romana; Stulik, Jiri (Frontiers in Immunology, 2023)
Francisella tularensis influences several host molecular/signaling pathways during infection.Ubiquitination and deubiquitination are among the most important regulatory mechanisms and respectively occur through attachment or removal of the ubiquitin molecule. The process is necessary not only to mark molecules for degradation, but also, for example, to the activation of signaling pathways leading to pro-inflammatory host response. Many intracellular pathogens, including Francisella tularensis, have evolved mechanisms of modifying such host immune responses to escape degradation. Here, we describe that F. tularensis interferes with the host’s ubiquitination system. We show increased total activity of deubiquitinating enzymes (DUBs) in human macrophages after infection, while confirm reduced enzymatic activities of two specific DUBs (USP10 and UCH-L5), and demonstrate increased activity of USP25. We further reveal the enrichment of these three enzymes in exosomes derived from F. tularensis-infected cells. The obtained results show the regulatory effect on ubiquitination mechanism in macrophages during F. tularensis infection.